2004
DOI: 10.1124/dmd.32.4.398
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON OF PREDICTION METHODS FOR IN VIVO CLEARANCE OF (S,S)-3-[3-(METHYLSULFONYL)PHENYL]-1-PROPYLPIPERIDINE HYDROCHLORIDE, A DOPAMINE D2 RECEPTOR ANTAGONIST, IN HUMANS

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The purpose of this study is to investigate reliable prediction methods for in vivo pharmacokinetics and the likelihood of drug interactions with several cytochrome P450 inhibitors in humans for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In addition, we used Sprague-Dawley rats implanted with both jugular and portal vein cannulas. The estimates of CL and V ss of PNU96391 in the jugular vein were 2.4 l/h/kg and 2.7 l/kg, respectively, in the present study, which were very consistent with the values reported previously (Shobe et al, 2000;Yamazaki et al, 2004). Thus, the effects of the cannula implantation into both jugular and portal veins on the pharmacokinetics of PNU96391 seem to be negligible.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, we used Sprague-Dawley rats implanted with both jugular and portal vein cannulas. The estimates of CL and V ss of PNU96391 in the jugular vein were 2.4 l/h/kg and 2.7 l/kg, respectively, in the present study, which were very consistent with the values reported previously (Shobe et al, 2000;Yamazaki et al, 2004). Thus, the effects of the cannula implantation into both jugular and portal veins on the pharmacokinetics of PNU96391 seem to be negligible.…”
Section: Discussionsupporting
confidence: 82%
“…The hepatic availability (F h ) was estimated to be 43%, which was consistent with the oral bioavailability in jugular vein (F oral ϭ 40%) because the bioavailability in the portal vein (F a ⅐ F g ) was near complete (Ͼ90%). The blood/plasma concentration ratio of PNU96391 has been reported to be approximately unity (Yamazaki et al, 2004). Accordingly, the blood clearance of PNU96391 was calculated to be 2.4 l/h/kg, which accounted for approximately 60% of hepatic blood flow in rats (4.2 l/h/kg) (Lin et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Zuegge et al (2001) used allometric scaling with correction for in-vitro hepatocyte CL int to predict the CL H for 22 compounds, and found 68% of predictions within 2-fold error and a maximum error of 10-fold. Yamasaki et al (2004) demonstrated that in-vitro hepatocyte CL int -corrected allometric scaling, but not allometric scaling (with and without brain weight and MLP correction), predicted the human invivo CL of a low CL compound well. Terelius et al (2001) used allometry for both observed and scaled (from hepatocyte data) in-vivo data, and concluded that pooling of data from different sources (in-vivo and in-vivo) was required to accurately assess the uncertainty in the predictions.…”
Section: Allometric Scaling With Correction For Interspecies CL Int Amentioning
confidence: 95%
“…To improve the predictability of the allometric scaling principle, corrections for species differences in in-vitro CL int and/ or plasma f u have been included (Boxenbaum 1980;Bonati et al 1984;Sawada et al 1985;Chiou & Hsu 1988;Paxton et al 1990;Chiou & Choi 1995;Lavé et al 1995bLavé et al ,1996aLavé et al , b, 1997aLavé et al , 1999aObach et al 1997;Sanwald-Ducray & Dow 1997;van Hoogdalem et al 1997;Mahmood 1998;Richter et al 1998;Ward et al 1999;Feng et al 2000;Terelius et al 2001;Zuegge et al 2001;Luttringer et al 2003;Yamasaki et al 2004;Tang & Mayersohn 2005). Chiou & Hsu (1988) found good predictability of CL u (from rat to man) and poor predictability of CL for 15 extensively metabolized compounds.…”
Section: Allometric Scaling With Correction For Interspecies CL Int Amentioning
confidence: 99%
“…Among these parameters, CL plays a central role because it relates to both the drug's half-life (t 1/2 ) and oral bioavailability (F oral ), whereas V ss and F abs are also required to fully characterize the dosing regimen such as dose size and frequency. Methods of predicting CL in humans include species scaling by allometry (Boxenbaum, 1984;Mordenti, 1986;Ings, 1990), in vitro-in vivo extrapolation (IVIVE) (Houston and Carlile, 1997;Obach et al, 1997;Rostami-Hodjegan and Tucker, 2007), and the combined use of in vivo animal and in vitro human data (Ubeaud et al, 1995;Lavé et al, 1999;Yamazaki et al, 2004). Allometric scaling is simply based on the similarity of anatomical, physiological, and biochemical variables across species including humans.…”
Section: Introductionmentioning
confidence: 99%